2004
DOI: 10.1016/j.jcf.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides produced by Burkholderia cenocepacia recA lineages IIIA and IIIB

Abstract: Clinical and environmental strains of Burkholderia cenocepacia belonging to the recA lineages IIIA and IIIB were examined for exopolysaccharide (EPS) production. The exopolysaccharides structure was determined using mainly gas chromatography coupled to mass spectrometry and NMR spectroscopy. All the strains produced Cepacian, a highly branched polysaccharide constituted of a heptasaccharide repeating unit, composed of one rhamnose, one glucose, one glucuronic acid, one mannose and three galactose residues. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Second, we directly measured the weight of the exopolysaccharide produced by the wild-type and mutant Burkholderia strains. Because mannitol medium has been reported to induce the production of exopolysaccharide in Burkholderia cenocepacia (20), we cultured the strains in mannitol medium for 3 days and purified exopolysaccharide from the culturing media. The ⌬purT mutant strain produced significantly less exopolysaccharide than the wild-type and the ⌬purN mutant strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we directly measured the weight of the exopolysaccharide produced by the wild-type and mutant Burkholderia strains. Because mannitol medium has been reported to induce the production of exopolysaccharide in Burkholderia cenocepacia (20), we cultured the strains in mannitol medium for 3 days and purified exopolysaccharide from the culturing media. The ⌬purT mutant strain produced significantly less exopolysaccharide than the wild-type and the ⌬purN mutant strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial exopolysaccharide was purified from cell culture media by following a previously described method with modifications (20). Bacterial cells were grown for 3 days at 30°C in 10 ml of mannitol medium (0.2% yeast extract and 2% mannitol) containing rifampin.…”
Section: Methodsmentioning
confidence: 99%
“…The ring proton regions δ 3.0~4.2 showed overlapping peaks and were assigned to protons of carbons C2 to C5 (or C6) of the glycosidic ring. And the high field region δ 1.28, observed as two well-separated signals, contributed to the methyl groups of two kinds of glycosyl linkages of rhamnose residues (Chiarini et al, 2004;Cozzolino et al, 2006). Likewise, in their 13 C NMR spectra, a low-field intense signal at δ 175 corresponded to −CO 2 H of uronic acids (Simas et al, 2006).…”
Section: Chemical Characterizationmentioning
confidence: 97%
“…The hemicellulose subfraction H30 exhibited anomeric protons at 4.31, 4.50, and 5.16 ppm, which are assigned to nonsubstituted backbone of D-xylp units, 4-O-methyl-D-GlcpA attached via α-(1→2) linkage to xylose, and 4-O-methyl-D-GlcpA residues, respectively (Lisboa et al 2005). The relevant signals at 4.90 to 5.60 ppm are assigned to α-anomeric protons, and 4.30 to 4.90 ppm to β-anomers (Chiarini et al 2004). This confirmed that the xylose unit is linked β-glycosidically, which was in agreement with the presence of a small sharp peak at 899 cm -1 in the FT-IR spectra.…”
Section: Nmr Spectramentioning
confidence: 99%